2017
DOI: 10.1111/cmi.12725
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 70 promotes coxsackievirus B3 translation initiation and elongation via Akt-mTORC1 pathway depending on activation of p70S6K and Cdc2

Abstract: We previously demonstrated that coxsackievirus B3 (CVB3) infection upregulated heat shock protein 70 (Hsp70) and promoted CVB3 multiplication. Here, we report the underlying mechanism by which Hsp70 enhances viral RNA translation. By using an Hsp70-overexpressing cell line infected with CVB3, we found that Hsp70 enhanced CVB3 VP1 translation at two stages. First, Hsp70 induced upregulation of VP1 translation at the initiation stage via upregulation of internal ribosome entry site trans-acting factor lupus auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…In the elongation step, Hsp70 activates the Akt-mammalian target of rapamycin complex 1 (mTORC1) signal cascade, leading to activation of EEF2 via kinase p70S6K-and Cdc2-mediated phosphorylation and inactivation of EEF2 kinase (EF2K). 218 Hsc70 enhances the IRES activity in EV-A71 infected cells. Hsc70 interacts with 2A protease of EV-A71 to enhance EIF4G cleavage that impairs host cell cap-dependent translation but enhances viral IRES-mediated translation.…”
Section: The Function Of Hsp70 Family In Virus Infectionmentioning
confidence: 92%
See 2 more Smart Citations
“…In the elongation step, Hsp70 activates the Akt-mammalian target of rapamycin complex 1 (mTORC1) signal cascade, leading to activation of EEF2 via kinase p70S6K-and Cdc2-mediated phosphorylation and inactivation of EEF2 kinase (EF2K). 218 Hsc70 enhances the IRES activity in EV-A71 infected cells. Hsc70 interacts with 2A protease of EV-A71 to enhance EIF4G cleavage that impairs host cell cap-dependent translation but enhances viral IRES-mediated translation.…”
Section: The Function Of Hsp70 Family In Virus Infectionmentioning
confidence: 92%
“…Virus entry RNA virus: CAV-9, 186 EV-A71, 188 DENV, 110,189 JEV, 191 ZIKV 190,197 DNA virus: SV40, 234 AdV, 237 HSV, 241 polyomavirus 254 RT virus: HTLV-1, 258,259 HIV-1 260 Virus replication RNA virus: MuV, 201 CDV, 203,204 HCV, 206 RSV, 209 EBOV, 212,213 Influenza 217 Virus gene expression RNA virus: Coxsackievirus B3, 218 EV-A71, 219 Influenza A [222][223][224][225][226] DNA virus: Polyomavirus, JCV, HCMV, 245,[246][247][248][249] Assembly RNA virus: Reovirus, 227 Poliovirus, 228 Coxsackievirus B1, 228 Influenza 229 DNA virus: Polyomavirus 254 Virus release RNA virus: HCV 232,233 Cellular transformation DNA virus: SV40, [264][265][266][267]…”
Section: The Function Of Hsp90 Family In Virus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of HSF1 is controlled by phosphorylation. Studies have shown that CVB3 activates calcium/calmodulin-dependent protein kinase II (CaMKII), which phosphorylates HSF1 at serine 230 (Qiu et al, 2016; Wang F. et al, 2017). In this study, we determined the phosphorylation of HSF1 at serine 326, which also promotes the activation of HSF1 (Chou et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the expression levels of phosphorylated PI3K and AKT were reduced in PCI-13 cells transfected by ACTL8 siRNA. In addition, the downstream action target of the PI3K/AKT signaling pathway, p70S6K, serves a crucial role in translation initiation, cell metastasis, protein synthesis and cell cycle (27,28). Similarly, the expression levels of p70S6 K in the PI3K/AKT signaling pathway were deceased following si-ACTL8 transfection in the present study.…”
Section: Discussionmentioning
confidence: 99%